(untitled) (Journal of the College of Basic Education, 2022)
Prediction is one of the speech acts of assertives which has noticeable importance in religious texts said by prophets since it is considered an essential part of prophecy (web 3). This study is an attempt to make a contrast between the holy Bible (English texts) and Prophet Mohammed traditions (PBUH) (Arabic texts) concerning this speech act. The study aims at finding out the similarities and the differences between the English and the Arabic languages as far as prediction in religious texts is concerned. It is hypothesized that Arabic is more explicit in producing prediction in the religious texts. The findings of the study verify that Arabic is not only more explicit concerning the forms used to express prediction, but in the kinds of prediction and some other details.